PENGARUH K3 (KESELAMATAN DAN KESEHATAN KERJA) DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KINERJA KARYAWAN PADA PT. BAMBANG DJAJA - Naufal Naputra Ibrahim; Sulastri Irbayuni (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
This research intended to determine the impact of occupational safety&health and human resource competence towards employee performance at PT. Bambang Djaja. Quantitative approach used through simple random sampling technique with total 100 sample employees of PT. Bambang Djaja. The study takes data by distributing questionnaires. Some variables used independent variable, K3 (Occupational Safety and Health) (X1), Human Resource Competence (X2), and the dependent variable, Employee Performance (Y). The analytical tool used Partial Least Square (PLS) model. The results show there is a significants and positive affects between occupational safety&health and human resource on employee performance. The better the implementation of K3 and the superior competence possessed by employees, help the greatest performance of employees at PT. Bambang Djaja.